Analysis of Variable Speed PFC Chopper Fed BLDC Motor Drive - A Jeya Selvan Renius; K Vinoth Kumar (Institute of Advanced Engineering and Science, 2015)
This paper provides the detailed analysis of the DC-DC chopper fed Brushless DC motor drive used for low-power applications. The various methods used to improve the power quality at the ac mains with lesser number of components are discussed. The most effective method of power quality improvement is also simulated using MATLAB Simulink. Improved method of speed control by controlling the dc link voltage of Voltage Source Inverter is also discussed with reduced switching losses. The continuous and discontinuous modes of operation of the converters are also discussed based on the improvement in power quality. The performance of the most effective solution is simulated in MATLAB Simulink environment and the obtained results are presented.